Enhancing clinical success through intensive dietary support in bariatric patients: a retrospective study in Asian population - Sim, Alvina Xin Jie; Tsen, Poh Yue; Mohd Ngali, Nurhanis; Lim, Shu Yu; Gee, Tikfu; Hanipah, Zubaidah Nor (Springer, 2023)
Background Weight loss surgery is an established intervention for obesity and related conditions, ensuring sustained weight reduction and improved comorbidities. Post-bariatric surgery, maintaining nutritional adequacy and weight loss necessitates ongoing, intensive dietary support. This research aims to discern the impact of standard care vs. intensive dietary support on outcomes following bariatric surgery within an Asian demographic. This study aims to research the part that intensive dietary support plays in contrast to standard care in altering weight loss and BMI change following bariatric surgery.